Innovation of a Three-Dimensional (3D) Printed Video Laryngoscope for Difficult Airway Management in a Rural Setting - Hadiwijono, Vanessa Juventia; Muhammad, Emerald (Majalah Anestesia & Critical Care, 2025)
Background: Managing difficult airways remains a critical challenge in anesthetic practice, particularly in resource-limited settings. While modern video laryngoscopes are effective, their high cost and limited availability hinder their use in peripheral areas.Case Illustration: We report a 41-year-old woman with an abscess colli sinistra, classified as ASA III, who presented with a difficult airway requiring general anesthesia for surgical debridement. Due to anticipated intubation difficulty and limited access to advanced equipment, we employed an innovative 3D-printed video laryngoscope made of polyethylene terephthalate glycol (PETG), equipped with a endoscopic camera. The device facilitated successful endotracheal intubation without complications.Conclusion: TThis case highlights the potential of affordable, customizable 3D-printed video laryngoscopes as an alternative airway management tool in low-resource settings.